2018
DOI: 10.1016/j.tig.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression in Single-Cell Analysis: Saving Grace or Original Sin?

Abstract: As a fundamental unit of life, the cell has rightfully been the subject of intense investigation throughout the history of biology. Technical innovations now make it possible to assay cellular features at genomic scale, yielding breakthroughs in our understanding of the molecular organization of tissues, and even whole organisms. As these data accumulate we will soon be faced with a new challenge: making sense of the plethora of results. Early investigations into the replicability of cell type profiles inferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 77 publications
0
37
0
Order By: Relevance
“…To develop a strategy for denoising scRNA-Seq datasets containing a complex mixture of cell populations with unknown degrees of similarity, we observed that while true expression differences between cell types and subpopulations result in substantial gene-gene correlation structure 22,23 , sampling noise affects the expression measurement of each gene in a largely independent fashion. We therefore reasoned that principal component analysis (PCA), applied to variance-stabilized data 10 , could be a powerful approach for separating biological heterogeneity from technical noise in scRNA-Seq data.…”
Section: Resultsmentioning
confidence: 99%
“…To develop a strategy for denoising scRNA-Seq datasets containing a complex mixture of cell populations with unknown degrees of similarity, we observed that while true expression differences between cell types and subpopulations result in substantial gene-gene correlation structure 22,23 , sampling noise affects the expression measurement of each gene in a largely independent fashion. We therefore reasoned that principal component analysis (PCA), applied to variance-stabilized data 10 , could be a powerful approach for separating biological heterogeneity from technical noise in scRNA-Seq data.…”
Section: Resultsmentioning
confidence: 99%
“…As baselines, we computed (1) (Figure 5a,b). We reasoned that this result is due to more discoverable gene-gene interactions 284 (as captured by coexpression) within the pan-resolution setting because coexpression changes in 285 strength with clustering resolution 16,24 . We also note that this result is not limited to the multi-286 study integration setting but can, in principle, also increase discovery of coexpressed genes 287 within a single study.…”
Section: Interpretation Of Coexpression Landscape Yields Insight Intomentioning
confidence: 99%
“…Moreover, biological signal in multi-study analysis is 13 confounded by study-specific noise patterns. This problem has motivated techniques for 14 computational batch effect correction [9][10][11][12][13][14][15] , but existing approaches integrate experiments using 15 transformations that obscure the biological relevance of individual data values, making it 16 difficult for downstream analyses to interpret the transformed result. Existing integrative 17 algorithms also aim to minimize inter-study variation, thus removing relevant differences that 18 would otherwise be useful to biological researchers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations